A Novel Real-Time PCR Method for Determination and Quantification of Each Cytomegalovirus Glycoprotein H Subtype in Clinical Samples - Ikuta, Kazufumi (American Society for Microbiology, 2012)
To investigate reinfection in patients with congenital cytomegalovirus (CMV) infection, we established a CMV subtype-specific real-time quantitative PCR method targeting the CMV gH epitope region that can be used for evaluating pathogenic CMV strains in cases of mixed CMV infection.